A Comparative Study of The Communication Behaviors of Popular and Neglected Preschool Children - SU, RINA (Pacific International Journal, 2022)
In this study, I developed a communication behavior observation form and used it as a research tool to analyze and compare the communication behaviors of three popular preschool children and three neglected preschool children. The results revealed both commonalities and significant differences in the communication behaviors of popular and neglected preschool children, with significant differences in the dimensions of communication behavior context, willingness level of communication behavior, the emotional attitude of communication behavior, the object of communication behavior, function of communication behavior, and outcome of communication behavior（P＜0.05）. There were no significant differences in communication behavior relationships and communication behavior performance styles（P＞0.05）. Whether there were commonalities or differences, popular preschool children’s communication behaviors outperformed neglected preschool children’s communication behaviors on various dimensions.